Motivasi dan Kemampuan Individu dalam Mendukung Knowledge Sharing Dosen Tetap pada Perguruan Tinggi - Islamy, Fahmi Jahidah; Inayati, Tutik; Hernawan, Yosep; Nur’Alliah, Siti; Taopik, Aldi Rahmat (Universitas Pendidikan Indonesia (UPI), 2024)
This study aims to determine the effect of motivation on ability and its impact on knowledge sharing in the permanent lecturer of the Universitas INABA Bandung. The sampling method uses saturated samples. Data retrieval is done using a closed questionnaire to 51 permanent lecturers at Universitas INABA Bandung. The analysis technique used in this study is path analysis. The results showed that motivation had a positive and significant effect on ability, motivation had a positive and significant effect on knowledge sharing, ability did not significantly influence knowledge sharing, and motivation and ability had a positive and significant effect on knowledge sharing.